PENGARUH DINAS MALAM TERHADAP KESEGARAN JASMANI PERAWAT - Ulfa, Ana Farida (Eduhealth, 2010)
Abstract Physical freshness is a possibility and capability to do adaptation towards physical burden ( from daily activity ) without emerge plentiful fatigue. A nurse, as one of healthy force also should have good physical freshness condition also, especially for them that doing shift work. Based on healthy survey and safety work, about 50% the caution of safety and healthy work is disturbed by an effect from the Nurses physical descent condition, especially for them that tread shift work. The goal of this research is to know the influence night shift towards physical freshness the nurse of night shift at Cempaka room Bapelkes RSD Jombang. This research use an analytic description research project, with cohort approach, that is time approach according to longitudinal, this research also named prospective research. The influence of night shift towards a physical freshness was examined by statistic with significant degree 0.05. The result from statistic test Two Way Anova  got significant value 0.08 which means there is no an influence between night shifts with physical freshness for Nurse at Cempaka room Bapelkes RSD Jombang. The descent of physical freshness in Cempaka room influenced by big burden work and the nurse tread it for a long time. The other important factor is the nurse in Cempaka room never does sport after night shift. While the function of sports it self are increasing the power resistance of Cardio Vascular and breathing system, the amount of erythrocyte and blood volume increase so that vitality and body power resistance will be good. And the nurse will easy to get back their physical freshness to do their daily activity. Keywords: Nurse of night shift, physical freshness.